Implementasi Nilai-Nilai Budaya Malaka Tebe Bei Mau dalam Konseling Lintas Budaya - Rohi, Enasely Mega Wenyi; Bone, Matilda Pia; Bulor, Rosa Mustika; Banu, Edigius Paulus (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2023)
This article describes the implementation of Malacca cultural values known as Tebe Bei Mau in the context of cross-cultural counseling. These values reflect the ethical principles, social harmony, and outlook on life inherent in Malacca culture. This research aims to investigate how these values can be applied in the cross-cultural counseling process to increase understanding, openness, and good relations between counselors and clients